A History of the Privileges of the Qur'an and Magical Receptions of it: A Concise Review of the Book of Wedha Mantra by Sang Indrajati - Yahya, Mohamad (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
The material object of this article is the magical reception of the Qur'an described in the Wedha Mantra by Sang Indrajati. The academic problem proposed is the distance between the Qur'an as an Arabic holy book and the Indonesian people who are far from the Arab country and are not Arabic speakers. This distancing gives rise to the phenomenon of magical reception. As a brief reading, the method used is a textological study by tracing its discursive tradition through hadith literature. The findings in this article are threefold. First, in the hadith literature, the issue of the privileges of the Qur'an still pays attention to the harmony and content of the text. Second, when the Qur'an penetrates the world far from the area of decline, the potential for perception beyond its textual function becomes very significant. The user's attention is precisely on the harmony of the sound aspect and the desired desire. Third, magical worship of the Qur'an is carried out in the interest of fulfilling the psycho-biological needs of the worshipper.